Seismic crosshole data and direct push-based hydraulic and electrical properties of a near surface aquifer at the TestUM site in Wittstock/Dosse (Germany) - methane gas injection experiment - Marco Pohle; Susann Birnstengel; Helko Kotas; Simon Kögler; Kilian Peisker; Andreas Schoßland; Jonathan Schultz; Ulrike Werban (PANGAEA, 2022)
The data set consists of eight crosshole seismic data sets obtained with a sparker source and two hydrophone string receivers in a near surface aquifer at the TestUM site in Wittstock/Dosse (Germany). The data has been collected before and after a methane gas injection experiment from April 2019 to May 2020. Therefore the data set comprises one baseline and seven monitoring measurements. Data collection was performed using a seismic sparker (borehole source SBS42, Geotomographie, Neuwied, Germany) as a source located in a 2” borehole operating at a depth between 8-13 m. The generator operated at frequency of 5 kHz. The hydrophone strings (Geotomographie, Neuwied, Germany) were placed each in a 2” borehole at a depth between 8-13 m covering a hydraulically low permeable layer between 9-11 m depth and part of the sandy aquifer down to 13 m depth. The data set is supplemented with additional information about the in situ hydraulic and electrical properties at three locations in the vicinity of the test site. These data were collected by using Hydraulic Profiling Tool (Geoprobe, Geoprobe Systems, Salina, KS, USA) obtaining the relative hydraulic conductivity. The in situ electrical properties where obtained depth-oriented with the Wenner-array with an EC probe (SC-500, Geoprobe Systems, Salina, KS, USA).